Sustainability and firms' mission in a developing country: the case of voluntary certifications and programs in Costa Rica. Issue 11 (7th July 2022) - Valenciano-Salazar, Jorge A.; André, Francisco J.; Martín-de Castro, Gregorio
Abstract : Voluntary environmental and social certifications represent a channel by which firms can contribute to sustainable development. Using qualitative and quantitative methods, we explore the motivations and obstacles that Costa Rican companies face when adopting Carbon Neutral (CN) and Fairtrade (FT) certifications. CN is a domestic certification aimed at reducing or offsetting carbon emissions and fighting climate change. FT is a well-known international label that guarantees compliance with environmental and social standards. We conclude that ethical and environmental reasons influence the managers' decision, along with economic and strategic incentives, such as improving the image of the company and the relationship with stakeholders. High investment and certification costs are ranked as the most difficult obstacles to overcome. By exploring the differences between both certifications, we find out that increasing sales, market shares or prices are more important motivations for the FT companies than for CN ones.